Instagram Content Engagement in Islamic Philanthropy: Evidence from BAZNAS Indonesia - Lusi Emawati; M Fahmi Hidayat; Rulli Kurniawan; Eneng Riska Rahayu Putri (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2026)
This study examines how Instagram content characteristics shape audience engagement in Islamic philanthropy, using BAZNAS Indonesia as a case. A quantitative content analysis was conducted on 544 organic posts published by @baznasindonesia from January to May 2025. Post type, publication timing, message interactivity, and post appeal were manually coded, and Ordinary Least Squares (OLS) models were estimated for log-transformed likes and comments. Entertainment appeal significantly increased likes (β = 1.451, p = 0.015) and comments (β = 2.176, p = 0.002). Posts published on public holidays received more likes (β = 0.441, p = 0.004), whereas images (β = −0.277, p = 0.015) and Reels (β = −0.510, p < 0.001) generated fewer likes than carousels. Message interactivity was not significant for either likes (p = 0.388) or comments (p = 0.365). The study contributes to Islamic communication and digital-philanthropy scholarship by showing that engagement is shaped not simply by calls to action, but by the interaction between format, timing, and ethically framed edutainment. It proposes a sharia-based edutainment strategy that combines attention-generating content with truthful, educational, dignified, and non-exploitative communication.